Simple Reading Activities - Hadfield, Jill; Hadfield, Charles (Oxford Oxford university press, 2010)
This book contains 30 activities at elementary level, all of them dealing with topics which form part of everybody's daily lives, for example families and leisure activities.
Activities.
Contents.
Keywords: Methodology; Language Learning; Teaching; Classroom techniques; English language